Hak Pendidikan bagi Pekerja Migran dalam Dinamika Globalisasi: Analisis Hukum Internasional dan Realitas Sosial - Afriansyah Tanjung; Dinda Riskanita; Maela Khoirul Ummah; Moh. Lubsi Tuqo Romadhan (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
This study examines the rights to freedom of association and education for Indonesian migrant workers (PMI) within international and domestic (Hong Kong and Indonesia) legal frameworks. The research questions focus on how legal norms regulate these rights and the structural, cultural, and legal barriers faced by PMI. An empirical legal approach combines legislative analysis (UDHR Article 26, ICESCR Articles 13-14, ICMW Article 43, and Hong Kong local regulations) with a case study of PMI experiences. Primary data were collected from interviews with PMI, diaspora communities, and NGOs, while secondary data came from legal documents and reports. Descriptive qualitative analysis reveals that, despite international norms guaranteeing education rights, PMI face exploitation, long working hours, and limited employer support, restricting access. The Open University program offers opportunities, but success depends on individual initiative and community support. Collaboration between governments and NGOs is essential for inclusive education access.